Management plans, monitoring and assessment of marine protected area - North-East Asian Subregional Programme for Environmental Cooperation (NEASPEC); Subregional Office for East and North-East Asia; UN.ESCAP (North-East Asian Subregional Programme for Environmental Cooperation (NEASPEC), 2021)
This publication is a compilation of studies concerning the marine protected areas of the North-East Asian Marine Protected Areas Network (NEAMPAN) established under the North-East Asian Subregional Programme for Environmental Cooperation (NEASPEC). The network currently consists of 12 marine protected areas (MPAs) in China, Japan, the Republic of Korea (ROK) and the Russian Federation selected by the respective countries. The twelve marine protected areas of NEAMPAN are diverse, with their sizes ranging from less than 30 km2 (Changyi National Marine Ecology Special Protected Area, China; Suncheon Bay Wetland Protected Area in the Republic of Korea; and marine areas of Sikhote-Alin State Natural Biosphere Reserve in the Russian Federation) to over 600 km2 (Far-Eastern State Marine Biosphere Reserve (FESMBR) in the Russian Federation), locations covering subarctic (Shiretoko National Park in Japan; and FESMBR in the Russian Federation) to tropical climate zones (e.g., Shankou Mangrove National Marine Nature Reserve and Nanji Islands National Marine Nature Reserve, China). Naturally, there are vast variations among the NEAMPAN MPAs in their biological features, target species, and the anthropocentric impact on the protected areas. While the institutional set up of MPA sites varies within and across the countries, each MPA has its own management plans and systems to monitor its ecological status and to ensure conservation and appropriate use of the marine protected areas. Thus, the studies compiled here are intended to look into the management plansand monitoring of the MPAs in NEAMPAN and explore their linkages. Some of these features are highlighted below, although this report is not an attempt to make cross-country comparisons - given the diverse nature of institutional settings and the responsibilities in management of the target MPAs in the respective countries.